Pulmonary Rehabilitation in Canada: A Report from the Canadian Thoracic Society COPD Clinical Assembly. Issue 3 (2015) - Camp, Pat G; Hernandez, Paul; Bourbeau, Jean; Kirkham, Ashley; Debigare, Richard; Stickland, Michael K; Goodridge, Donna; Marciniuk, Darcy D; Road, Jeremy D; Bhutani, Mohit; Dechman, Gail
Abstract : BACKGROUND: Pulmonary rehabilitation (PR) is a recommended intervention in the management of individuals with chronic lung disease. It is important to study the characteristics and capacity of programs in Canada to confirm best practices and identify future areas of program improvement and research. OBJECTIVE: To identify all Canadian PR programs, regardless of setting, and to comprehensively describe all aspects of PR program delivery. The present article reports the results of the survey related to type of program, capacity and program characteristics. METHODS: All hospitals in Canada were contacted to identify PR programs. A representative from each program completed a 175-item online survey encompassing 16 domains, 10 of which are reported in the present article. RESULTS: A total of 155 facilities in Canada offered PR, of which 129 returned surveys (83% response rate). PR programs were located in all provinces, but none in the three territories. Most (60%) programs were located in hospital settings, 24% were in public health units and 8% in recreation centres. The national capacity of programs was estimated to be 10, 280 patients per year, resulting in 0.4% of all Canadians with chronic obstructive pulmonary disease (COPD) and 0.8% of Canadians with moderate to severe COPD having access to PR. COPD, interstitial lung disease, and asthma were the most common diagnoses of patients. The majority of programs had at least four health care professionals involved; 9% had only one health care professional involved. CONCLUSION: The present comprehensive survey of PR in Canada reports an increase in the number of programs and the total number of patients enrolled since the previous survey in 2005. However, PR capacity has not kept pace with demand, with only 0.4% of Canadians with COPD having access.